Community resources as curricular input for an experience-based work-oriented program - Pablo, Bernadette Samson
The study was made in relation to the development of the experimental curriculum of the UPIS in line with the redirection of basic education to national goals. Its particular focus was the Grade 10 Program, an experience-centered, multidisciplinary program meant to integrate all learnings from Kindergarten to Grade 9. A 2-part survey questionnaire was developed to gather the data for this study. A purposive sample consisting of a total of 220 students and 239 parents responded to the instrument. The findings of the present study indicate the feasibility of developing an experience-based component of the grade 10 program.